Dari Sikap Radikal Menuju Perilaku Terorisme : Deskripsi Perilaku Teroris di Kabupaten Lamongan - Nur Ika Fatmawati; Ahmad Farid (Universitas Islam Darul Ulum Lamongan, 2020)
The Indonesian state has lived and grown based on the diversity of ethnic groups, religions, beliefs and customs that have developed beyond the age of this republic. Because of these factors, the founders of this nation formulated the values ​​and philosophies of the nation which were abstracted in the Pancasila and also the opening of the Constitution as the basis of the country's constitution. One of the values ​​is tolerance and respect for the different. These values ​​are manifested in daily life or also manifested in policies that protect all citizens without exception. Unfortunately, over time and global developments that continue to change, these values ​​and principles eroded so that they become a source of social conflict. One of the problems that continues to emerge in the Indonesian public sphere is religious intolerance, radicalization and terrorism. Religious intolerance, radicalization and terrorism are manifested in the prohibition of religious worship activities, the spread of hatred, religious based violence or the destruction of places of worship. In addition to increasingly diverse forms of intolerance, the territory is also expanding. Initial studies show that there is a strong geographical link between the growth of religious intolerance and the recruitment of terrorist groups and ISIS. Religious intolerance has occurred in almost all regions of Indonesia, as well as the radicalization of religion and terrorism.